Handoff Scheme for Terrestrial Mobile and Satellite Convergence Networks with Incorporation of Pattern Recognition Algorithm - Kwong, Chiew Foong (2009)
As the communication becomes a global affair today, engineers had begin to look into the heterogeneous network solution for faster and cheaper deployment. For heterogeneous network to function properly, efficient and effective mobility management is vital to ensure uninterruptable and ubiquitous connection. Recently there has been many works done to replace the traditional handoff decision algorithm such as hysteresis and fuzzy logic based handoff algorithm, especially in the heterogeneous environment. The fuzzy handoff algorithm proposed by earlier work is not optimized and required constant attention from the human experts. This paper proposes a newer approach using Adaptive Network Fuzzy Inference System (ANFIS) where the training element is incorporated into the existing fuzzy handoff algorithm. This paper also discusses the effective mobility management strategy to suit the hybrid terrestrial and satellite segment.